Comparison of the Effectiveness of Various Doses of Ointment from a Dry Extract of Radix Glycyrrhizae in Contact Allergic Dermatitis - Akram, Suyarov; Khayrulla, Khatamov; Shukhrat, Ziyadullaev; Sherzod, Mukhtorov; Malika, Foziljonova (International Journal of Psychosocial Rehabilitation, 2020)
It was established when comparing the effectiveness of different doses of ointment obtained from dry extract of radix glycyrrhizae in different doses, 5% ointment provides a more effective treatment of contact allergic dermatitis than 1%, 3% of the dose of this ointment, psilo-balm and topical celestoderm B. Accordingly, the index of reduction in severity of skin manifestations (Ind) was higher in this group than in others. All studied doses: 1%, 3% and 5% ointments of radix glycyrrhizae extract significantly reduced the thickness of the skin fold compared with the control group. Of the three doses of ointment, 5% ointment removed the swelling of the skin fold to its original position by 11th day than other doses of the ointment.